Criminal Policy on Tobacco Excise at North Sumatra Regional Office of The Directorate General of Customs and Excise (DGCE) - Nantama Mulyana; Taufik Siregar; Rizkan Zulyadi (Pelopor Publikasi Akademika, 2023)
This research was conducted to discuss the criminal policy on tobacco excise at North Sumatra Regional Office of the DGCE. The phenomenon of increasing excise rates every year does not reduce tobacco consumption in Indonesia but instead increases the circulation of illegal tobacco products. The research method used is normative juridical research supported by empirical data and interviews. The nature of this research is descriptive analysis. The results of the research on the policy of combating tobacco excise criminal offenses at the North Sumatra Regional Office of the DGCE refer to Law No. 11 of 1995 as last amended by Law No. 7 of 2021, Minister of Finance Regulation No. 237/PMK.04/2022, and DGCE Instruction No. INS-05/BC/2022 dated November 1, 2022. The North Sumatra Regional Office of the DGCE has not yet resolved tobacco excise criminal cases with restorative justice from 2021 to 2022. The obstacles faced by the North Sumatra Regional Office of the DGCE include the absence of implementing regulations for the law, the failure to implement the roles of Customs and Excise investigators, inadequate facilities and infrastructure, low legal awareness of the public, smoking culture, and negative perceptions of tobacco excise regulations.